MICRO DETERMINATION OF DOPAMINE IN BIOLOGICAL SAMPLES BY COUPLING REACTION - AHMED JASSIM MUKLIVE AL-OGAIDI (Journal of Engineering Studies and Research)
The paper presents the development of an analytical method to determine dopamine by coupling reaction with diazotized solution of 4-Aminoantipyrine in basic media to give a compound with a single azo dye salt having orange color soluble in water. A calibration curve for a range of concentration (9.14x10-5 – 2.28x10-3 μg.mL-1) was realized and the value of molar absortivity was 1.5x103 L.mol-1.cm-1, with a relative standard deviation more than 1.26% and a recovery 98.77%. As we study the nature of the azo dye by mole fraction method, from the practical value we found that the mole fraction of the dye compound is 1:1 (dopamine: 4- amino antipyrine) and the stability factor reach to 1.4x106 L.mol-1. The described procedure is very simple, low-time-consuming, provides high throughput of examined samples, and could be used for routine screening and confirmatory analyses as well. The method was successfully validated to the analysis of the dopamine in biological samples.